Pendampingan Pembuatan Laporan Keuangan Di Kelurahan Maguwoharjo Dengan Menggunakan Metode Akrual (Ms.Excel) Sederhana - Monika Monika; Zaenal Wafa (Institut Nalanda, 2023)
Financial reports are very important for the Maguwoharjo Village, especially for the public sector in terms of public accounting which leads to reports that provide accountability and transparency to the general public so that there is no more fraud and it can be easily understood by the community. In this service the method used is a direct field survey, support and results. The results of assisting in the preparation of these financial reports are simplified by the accrual method through MS.excel which can provide an understanding of where the income and expenses are obtained by the Maguwoharjo Village each year.